Keterampilan Guru Pendidikan Jasmani dalam Penggunaan TIK terhadap Pembelajaran Daring - OETOMO, GANJAR PANJI; Hartono, Mugi (Universitas Negeri Semarang, 2023)
The Covid-19 pandemic has had a huge impact on changes, one of which is in the field of education. The more ferocious the outbreak that attacked the central government, it urged all educational institutions to carry out distance learning or called online learning. These conditions and regulations must also be implemented by elementary school physical education teachers in Subah District. Therefore, elementary school physical education teachers must have ICT skills to support the ongoing online learning process.This study uses a qualitative approach. The subjects in this study were all physical education teachers in elementary schools in Subah Sub-district, of which a total of 31 physical education teachers in 31 elementary schools. Collecting data using the instrument sheet Physical Education Teachers Subjective Theories (PETSTQ) using survey data collection methods for physical education teachers.